Determination of fungal genera composition and total toxicity of feed produced in the Republic of Crimea - S. S. Ibragimova; O. V. Pruntova; S. I. Danilchenko; Ye S. Yerofeeva (Ветеринария сегодня)
Animal mycotoxicoses caused by ingestion of toxicogenic micromycete-contaminated feed are of major concern for agricultural industry and of great importance for production of agricultural products. In 2017–2019, feed and raw feed materials produced in the Republic of Crimea were tested for mold fungi and genera composition thereof; the feedstuffs were tested for total toxicity by bioassay in rabbits. A total of 252 samples including 124 grain feed samples, 70 forage samples, 58 mixed feed samples were selected for testing. Tests showed that the major detected contaminants were members of the following genera: Mucor (67.9%), Penicillium (26.6%), Aspergillus (13.1%), Fusarium (9.1%), Alternaria (8.7%), Stachybotrys (3.6%) and Rhizopus (2.0%). It was revealed that feed were exposed to mold fungi contamination during vegetation and harvesting as well as during transportation and storage. Thus, in spring the feed were more often contaminated with micromycetes of Penicillium genus (37.8%) and Stachybotrys genus (6.7%); feed collected and tested in autumn were more often contaminated with toxicogenic mold fungi of Fusarium genus (14.9%), Alternaria genus (13.9%) and Rhizopus genus (3.0%); in winter members of Mucor genus (78.0%) and Aspergillus genus (22.0%) were most often detected in feed. Tests for determination of total toxicity showed that 9 (7.3%) and 10 (8.1%) samples out of 124 tested grain feed samples were low toxic and evidently toxic, respectively. Tests of mixed feed samples for toxicity showed that 5 samples (8.6%) and 2 (3.4%) samples out of 58 mixed feed samples were low toxic and evidently toxic, respectively. It was shown that the proportion of contaminated feed was the highest in spring (25.0%) as compared to proportion of the contaminated feed in winter (18.2%), in autumn (13.7%) and in summer (4.5%).